ANALYSIS OF IGNORANCE AND ENLIGHTENMENT IN THE WORKS OF YUSUF KHOS HAJIB (Universal International Scientific Journal, 2026)
This article analyzes the artistic and philosophical interpretation of the issue of ignorance and enlightenment in the work of Yusuf Hos Hajib, a major figure in Turkish classical literature. In particular, the ideas of knowledge, reason, justice, and spiritual perfection are studied in the example of the writer's famous work - Kutadgu bilig. The work shows ignorance as a factor that hinders the development of man and society, and enlightenment is interpreted as the main value that forms a perfect person. The research uses historical, literary, and philosophical analysis methods.
Keywords: ignorance, enlightenment, perfect man, Turkish literature, moral and philosophical views, public administration, science.